Methodology of Teaching in a Multilingual Environment: Challenges and Solutions - Kaliuzhna, Yuliia (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2026)
The research is directed toward a systematic comprehension of contemporary challenges and practical responses arising in instruction within a multilingual environment, as well as toward the development of a conceptual integrative model. The methodological basis consists of systems analysis and metasynthesis of scientific publications devoted to translanguaging, Content and Language Integrated Learning (CLIL) and the use of digital educational technologies. The analysis made it possible to identify key difficulties: cognitive overload of learners, insufficient preparedness of teachers, subjectivity of existing assessment systems and barriers to social integration. As a response the Synergetic Model of Multilingual Pedagogy (SMMP) is proposed, synthesizing pedagogical, technological and sociocultural approaches. SMMP integrates the principles of translanguaging and CLIL, strengthening them with digital didactic tools and forming a supportive, inclusive educational ecosystem. The results obtained confirm the hypothesis that the comprehensive implementation of these approaches can improve academic performance and facilitate the successful adaptation of learners. The presented material will be useful to educational researchers, methodologists, administrators of educational institutions and policymakers shaping the educational agenda.